KONFLIK BATIN DAN NILAI PENDIDIKAN NOVEL DI TANAH LADA KARYA ZIGGY ZEZSYAZEOVIENNAZABRIZKIE SERTA RELEVANSINYA DENGAN PEMBELAJARAN SASTRA DI SMA - Imani, Wafda Nurul; Wardani, Nugraheni Eko; Waluyo, Herman J. (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This study aims to describe: (1) characterization of the characters; (2) id from the inner conflicts of the characters; (3) ego from the inner conflicts of the characters; (4) super ego from the inner conflicts of the characters; (5) educational value; and (6)  the relevance of novels Di Tanah Lada as the study for literacy in high school.  The method used is descriptive qualitative.  The sources come from documents and informants.  The sampling technique uses purposive sampling.  Writer used document analysis and interview techniques to collect data.  Validation of the data is done by theory of triangulation and source triangulation. Analysis of the data used an interactive analysis technique.  The results of the study can be described as follows.  (1) The character of the characters in the novel Di Tanah Lada is varied, both in terms of character types and physiological, psychological and sociological dimensions;  (2) Id in the inner conflict experienced by the character includes the pleasure of labeling others, conforming wild thoughts in the head, ignoring parental advice, and indulging indulgence in pleasure;  (3) The ego in the inner conflicts experienced by the characters includes fulfilling curiosity and feeling guilty for the decision that's been taken;  (4) Superego in the inner conflicts experienced by the characters include, recognizing the risk of his decision, succumbing to the common good, helping people in trouble, accepting the risk of their actions;  (5) Educational values in drama scripts consist of religious, moral, social and cultural education values.  The value of education is being dominated by the value of social education;  (4) Novels Di Tanah Lada has been meet the standards for content, language, presentation, and graphic worthiness and can be pertained in literacy learning in class XI.